Store-operated Ca2+ entry regulatory factor alters murine metabolic state in an age-dependent manner via hypothalamic pathways. Issue 3 (4th March 2023) - Gataulin, Diana; Kuperman, Yael; Tsoory, Michael; Biton, Inbal E; Nataniel, Tomer; Palty, Raz; Karbat, Izhar; Meshcheriakova, Anna; Reuveny, Eitan
Abstract: Store-operated calcium entry (SOCE) is a vital process aimed at refilling cellular internal Ca 2+ stores and a primary cellular signaling driver for transcription factors' entry to the nucleus. SOCE-associated regulatory factor (SARAF)/TMEM66 is an endoplasmic reticulum (ER)-resident transmembrane protein that promotes SOCE inactivation and prevents Ca 2+ overfilling of the cell. Here, we demonstrate that mice deficient in SARAF develop age-dependent sarcopenic obesity with decreased energy expenditure, lean mass, and locomotion without affecting food consumption. Moreover, SARAF ablation reduces hippocampal proliferation, modulates the activity of the hypothalamus–pituitary–adrenal (HPA) axis, and mediates changes in anxiety-related behaviors. Interestingly, selective SARAF ablation in the hypothalamus's paraventricular nucleus (PVN) neurons reduces old age-induced obesity and preserves locomotor activity, lean mass, and energy expenditure, suggesting a possible central control with a site-specific role for SARAF. At the cellular level, SARAF ablation in hepatocytes leads to elevated SOCE, elevated vasopressin-induced Ca 2+ oscillations, and an increased mitochondrial spare respiratory capacity (SPC), thus providing insights into the cellular mechanisms that may affect the global phenotypes. These effects may be mediated via the liver X receptor (LXR) and IL-1 signaling metabolic regulators explicitly altered in SARAF ablated cells. In short, our work supports both central and peripheral roles of SARAF in regulating metabolic, behavioral, and cellular responses.